Analisis Framing Robert N. Entman Pada Pemberitaan Ferdy Sambo Saat Divonis Hukuman Mati Di Media Online Kompas.Com Periode 13 Februari 2023 - Dadan Saputra; Fani Rahmasari; Aulia Asmarani; Nugroho Iman Santoso (KOMVERSAL, 2024)
The news about Ferdy Sambo has become one of the news stories that has attracted public attention since it started appearing in the media, especially online media. In the February edition last month, this report became the main trending topic, which became one of the news stories that the wider community was looking forward to because it involved officials figures who well known among the public. This research was conducted using Robert N. Entman’s framing analysis method with a qualitative approach through its four elements, whish include : define problem, diagnose causes, make moral judgement, and treatment recommendation. The results of this research show that define problem on the online media Kompas.com is an attempt to construct news about Ferdy Sambo when he was sentenced to death on February 13 2023. The results of this research show that the define problem on the online media Kompas.com is how Kompas.com constructs the news Regarding Ferdy Sambo when he was sentenced to death, it became one of the news stories that was trending in online media, so every thing that Ferdy Sambo did while on trial would be framed as news. Diagnose Causes : Kompas.com highlights news about statements that will give rise to pros and cons in society so that the framing of the news will be interesting enough to interest readers. Make Moral Judgement : However, Kompas.com also writes that the judge’s decision is the main thing and must be respected. Treatment recommendation : it is important for the public to choose accurate and trustworthy news. Through the findings of this research, it is hoped that online media will continue to convey positive news in order to foster an optimistic attitude in the community.